The status of agricultural economics in East and Southern/Central Africa: proceedings of stakeholder workshop - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
The objectives of the conference were to:; Assess the ability of academic institutions to produce well-trained M.Sc. and Ph.D. agricultural economists and to conduct research;; Review existing training programs for their suitability, strengths and weaknesses, and indicate the areas needing attention;; Evaluate the market for agricultural economists, focusing on supply gaps, and provide some indicators of demand for them;; Suggest and evaluate ways to improve agricultural economics training capacity in the region. The main objective of the stakeholder workshop was to discuss the consultants’ report and to pave the way forward. In addition, a number of presentations on initiatives that are proposed or are being implemented in the region that contribute to strengthening of capacity in agricultural economics were made. Workshop participants were mainly drawn from the various institutions visited by the consultants during the study, i.e. university agricultural economics and economics departments, national agricultural research stations, policy research institutes, and networks.